Beyond Foreign Aid in Africa: Is a New Narrative Emerging? - Hyden, Goran (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
Narratives drive politics. Controlling how reality is understood and can be changed gives power and influence over development. For the last four decades African countries have to a large extent lived off the generosity of the international donor community. The cost of doing so has been obvious: the imperative to follow policy prescriptions that have worked elsewhere and for that reason alone have been treated as relevant and helpful also for Africa. This liberal internationalist approach has been centred on the twin principles of free market and democratic governance. It has served as dominant policy narrative with many governments in Africa embracing it as the way forward. It still has its supporters but the interesting thing about Africa today is that cracks are emerging in this intellectual edifice, thus rendering the narrative less compelling and less attractive.